Culture and Belonging in Divided Societies : Contestation and Symbolic Landscapes - Ross, Marc Howard (EBL-Schweitzer, 2009)
Why do people invest so much emotional energy and resources in conflicts over images, symbols, rituals, and other cultural expressions? The answers explored in Culture and Belonging in Divided Societies view such expressions as barriers to or opportunities for inclusion in a divided society's symbolic landscape and political life.